Development of a nutritional profile predicting tool for fresh and processed tomato‐based products. (20th April 2015) - Ayari, Asma; Achir, Nawel; Servent, Adrien; Ricci, Julien; Brat, Pierre
Summary This study was aimed at developing a tool to represent the evolution of nutritional profile of food during processing with input data mined from previous published papers or database on composition and reactivity of nutrients, and from minimal experimentations. Tomato‐based products, that is tomato sauce, concentrate and paste, were chosen to evaluate the developed model. The SAIN‐LIM system was used to assess the nutritional profile of the tomato products throughout the process steps, including seven constituents: five basic nutrients (i.e. proteins, fibres, vitamin C, calcium and iron) and two microconstituents found in tomato: β‐carotene and lycopene. The SAIN‐LIM nutritional profiles obtained with this model were compared to that calculated from experimental data. Calculated and experimental nutritional scores showed that process steps involved in tomato‐based products did not affect substantially their nutritional quality. Observed differences were mainly attributed to the kinetic parameter selection and raw product variability. The conclusion offers suggestions to extend the model to other product/process combinations.